2020
DOI: 10.1016/j.heliyon.2020.e05274
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of pesticide contaminants in tissue matrices of dogs suffering from malignant canine mammary tumors in Punjab, India

Abstract: The unprecedented application of pesticides in Punjab, India during green revolution has lead to an environmental crisis due to the accumulation of persistent organic and pesticide pollutants in the environment and biota of this region. The present study aimed at estimating the abundance of pesticide contaminants in three biological matrices of 36 dogs suffering from malignant canine mammary tumor (mCMT) and 6 tumor free control dogs from Punjab, India. Presence of individual and total pesticides in canine bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 67 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…Dogs and cats develop chronic diseases similar to those of humans but with a shorter latency period ( Knapp et al, 2013 ). Pesticide exposure in dogs and cats has been linked to mammary cancer ( Gautam et al, 2020 ), lymphoma ( Takashima-Uebelhoer et al, 2012 ), bladder cancer ( Glickman et al, 2004 ), and oral squamous cell carcinoma ( Bertone et al, 2003 ), reflecting effects similar to those reported in human studies ( Calaf, 2021 ; Fritschi et al, 2005 ; Koutros et al, 2016 ). Nevertheless, studies reporting the occurrence of pesticides in dog urine are limited ( Forster et al, 2014 ; Karthikraj and Kannan, 2019 ; Knapp et al, 2013 ; Reynolds et al, 1994 ; Wise et al, 2022 ), and no previous studies have determined the exposure of cats to OPs, neonics, PYRs, or PAs.…”
Section: Introductionmentioning
confidence: 67%
“…Dogs and cats develop chronic diseases similar to those of humans but with a shorter latency period ( Knapp et al, 2013 ). Pesticide exposure in dogs and cats has been linked to mammary cancer ( Gautam et al, 2020 ), lymphoma ( Takashima-Uebelhoer et al, 2012 ), bladder cancer ( Glickman et al, 2004 ), and oral squamous cell carcinoma ( Bertone et al, 2003 ), reflecting effects similar to those reported in human studies ( Calaf, 2021 ; Fritschi et al, 2005 ; Koutros et al, 2016 ). Nevertheless, studies reporting the occurrence of pesticides in dog urine are limited ( Forster et al, 2014 ; Karthikraj and Kannan, 2019 ; Knapp et al, 2013 ; Reynolds et al, 1994 ; Wise et al, 2022 ), and no previous studies have determined the exposure of cats to OPs, neonics, PYRs, or PAs.…”
Section: Introductionmentioning
confidence: 67%
“…Environmental exposures to various pesticides have been linked to many chronic diseases, including various cancers, diabetes, reproductive and neurological diseases, and birth defects. However, such exposures are not only a human health concern but they also present a veterinary health concern. Estimates suggest that between 38 and 50% of U.S. households have at least one pet dog. , Pesticide exposure has been linked to several diseases in pet dogs including lymphoma, mammary, and bladder cancers. , Pesticides used in lawn care, particularly the herbicide 2,4-D, have been reported to be associated with lymphoma in dogs. Dogs in India with mammary cancer had higher levels of total pesticides (which include fipronil and permethrin) measured in mammary tissues (β = 4.99) . Also, two studies have reported that dogs diagnosed with bladder cancer (transitional cell carcinoma) were significantly more likely to experience greater exposure to household insecticides , and lawn herbicides, particularly phenoxy herbicides .…”
Section: Introductionmentioning
confidence: 99%
“…Estimates suggest that between 38 and 50% of U.S. households have at least one pet dog. 11,12 Pesticide exposure has been linked to several diseases in pet dogs including lymphoma, 13−16 mammary, 17 and bladder cancers. 18,19 Pesticides used in lawn care, particularly the herbicide 2,4-D, have been reported to be associated with lymphoma in dogs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When rats were exposed to aldrin over a period of time, the relative liver weight increased significantly, and the survival rate of female rats decreased ( Adam et al, 2015 ). In Punjab, India, bioaccumulation of 14 pesticides, including dieldrin and aldrin, has been found in the tissue stroma of dogs with malignant canine breast tumors ( Gautam et al, 2020 ).…”
Section: Toxicity Of Aldrin and Dieldrinmentioning
confidence: 99%